Monetary policy, determinacy, and the natural rate hypothesis - Alexander Meyer-Gohde (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2011)
Imposing the natural rate hypothesis (NRH) can dramatically alter the determinacy bounds on monetary policy by closing the output gap in the long run. I show that the hypothesis eliminates any role for the output gap in determinacy and renders the conditions for determinacy identical for all conforming supply equations. Specializing further to IS demand, determinacy depends only on the parameters in the interest rate rule and a pure forward or backward-looking inflation target is inconsistent with determinacy. Monetary policy that embodies the Taylor principle with respect to contemporaneous inflation delivers a determinate equilibrium in all models that satisfy the NRH.
Keywords: C62; E31; E43; E52; 330; determinacy; natural rate hypothesis; Phillips curve; Taylor Principle; Geldpolitik; Taylor-Regel; Natürliche Arbeitslosigkeit; Phillips-Kurve; Neukeynesianische Makroökonomik; Theorie